Identification of Chemical Compounds of Ocimum basilicum (L.) Essential Oil and Cymbopogon nardus (L.) Rendle Essential Oil Using Gas Chromatography- Mass Spectrophotometry (GC-MS) - Dasmyta, Eny; Anwar, Yelfi; Maryan, Roni; Muryanto, Muryanto (BIOEDUKASI, 2024)
Essential oils are also commonly known as flying oils which can generally be obtain from roots, plant parts, bark, leaves, stems, seed fruits, and flower by steam distillation. The aim of the research is to determine the chemicals components of essential oils of basil (Ocimum basilicum L.) and citronella (Cymbopogon nardus (L.) Rendle) leaves obtained from farmers and processors in Karanganyar, Central Java. Essential oil composition was analysis use gas chromatographys-mass spectrophotometry (GC-MS) method. The finding explain namely chemical component of basil leaf essential oil show that the main component were Estragole (55.80%) and Linalool (22.35%), while in citronella essential oil show that the main component were Geraniol (26.49%), Citronellol (14.53%) and Citronellal (10.95%).